Janus nanoparticle compatibilizer as well as preparation method and application thereof
The Janus nanoparticles prepared through the lotion reaction, the anchor of the polymer interface through the melting co -mixing method solves the problem of unsatisfactory dispersion of Janus nanomaterials, and achieves good capacity increase and foaming performance.
Patent Information
- Application Number
- CN202411769320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-28
AI Technical Summary
The dispersion of existing Janus nanomaterials in blends is not ideal and prone to agglomeration, resulting in the failure to fully exert the capacity enhancement effect and difficult to meet the complex needs of different blend systems.
Prepare a polystyrene at one end through the emulsion reaction, and the other end of the branches of the epoxy base group of the epoxy group. Essence
A good effect of increasing the effect is achieved, the compassion and separation of the polymer suppress the three -dimensional three -dimensional network structure, and improves the foaming performance of the mixture.
Smart Images

Figure CN119371615A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a Janus nanoparticle compatibilizer and a preparation method and application thereof. Background Art
[0002] With the vigorous development of social economy, polymer materials are widely used in various fields of life due to their low cost and excellent performance. Polymer blending technology, as an effective means to improve material performance, achieves performance improvement by optimizing the combination of different polymers. However, problems such as phase coarsening and phase separation caused by the incompatibility between polymers pose challenges to material performance, especially in the supercritical carbon dioxide foaming process. Therefore, solving the compatibility problem after blending becomes the key.
[0003] Polylactic acid (PLA), as a representative of bio-based degradable materials, is gradually replacing traditional plastics with its green and environmentally friendly characteristics and excellent degradation performance. It is widely used in packaging, tableware and other fields to reduce environmental pollution. Polystyrene (PS) occupies an important position in the industry with its unique physical and chemical properties and cost advantages. Its high temperature stability and processing flexibility make it an ideal material for manufacturing complex structural products such as automotive parts and electronic products.
[0004] However, biodegradable polylactic acid (PLA) and polystyrene (PS) are incompatible, and phase coarsening will occur after direct blending. Therefore, the incompatibility of biodegradable polylactic acid (PLA) and polystyrene (PS) and the phase separation state after blending greatly limit their promotion and use in application fields such as tableware and daily packaging products. In the supercritical carbon dioxide foaming process, in order to increase the adsorption rate and saturation of the polymer to supercritical carbon dioxide, the temperature is usually increased, but when the temperature rises, the phase coarsening phenomenon will be further aggravated.
[0005] In the actual production process, in order to optimize the compatibility between the components of the blend, the strategy of introducing multiple compatibilizers is widely adopted.
[0006] Inorganic nanoparticles have a high specific surface area and are widely used in rubber toughening, plastic anti-aging and other fields. In recent years, researchers have developed new uses for nanoparticles in polymer volume expansion.
[0007] Inorganic nanoparticle compatibilizers are a type of material that utilizes the properties of inorganic nanoparticles to improve the compatibility of polymer blends. This type of compatibilizer usually has a high specific surface area and can be effectively distributed at the interface between the two phases of the polymer, thereby reducing the interfacial tension and improving the compatibility. For example, nano-SiO2 can be grafted with polymer chains or reactive groups due to the ease of modification of its surface hydroxyl groups to achieve compatibilization of the blend. Through surface modification, nanoparticles can be stably distributed at the interface to prevent agglomeration, thereby improving the performance of the blend.
[0008] However, inorganic nanoparticle compatibilizers also have some challenges, such as nanoparticle agglomeration and controlled distribution at the interface. In order to solve these problems, researchers have tried to improve the distribution stability of nanoparticles by grafting polymer chains or reactive groups on the surface, thereby achieving better compatibilization effects.
[0009] Janus nanoparticles are a type of central asymmetric particles with different surface chemical compositions and anisotropy. Compared with inorganic nanoparticle compatibilizers, organic-inorganic hybrid Janus nanoparticles not only have the advantages of inorganic nanoparticle compatibilizers such as high specific surface area and spatial effect, but are also easier to anchor at the interface of the two phases, entangle with the two-phase polymers on the molecular chain, form a three-dimensional network, and achieve a more excellent compatibilization effect. Chinese patent CN 103204508 A discloses a Janus material with dual properties and a preparation method thereof. Using polymer colloid particles as templates, through a seed emulsion polymerization method, based on interface self-assembly and phase separation mechanisms, organic / inorganic hybrid Janus particles are obtained, the organic end of which is a polymer containing double bonds such as polystyrene and polyacrylate, and the other end is an inorganic material. This type of Janus nanoparticle has a huge application prospect in polymer compatibilization. However, at present, the dispersion of Janus nanomaterials in blends is not ideal and they are easy to agglomerate, resulting in the failure to fully exert their capacity-increasing effect. During the preparation process, the structure and performance control of nanomaterials are not precise enough, making it difficult to meet the complex needs of different blending systems. There is also a lack of systematic research to deeply explore its impact on the foaming properties of blends. Summary of the invention
[0010] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a Janus nanoparticle compatibilizer and a preparation method and application thereof, so as to solve the problem that the existing Janus nanomaterial solubilizer has unsatisfactory dispersibility in blends and is easy to agglomerate, resulting in its compatibilization effect not being fully exerted and being difficult to meet the complex requirements of different blending systems.
[0011] To achieve the above object and other related objects, the present invention provides a method for preparing a Janus nanoparticle extender, characterized in that it comprises the following steps: (1) Adding styrene and an initiator to an emulsion system to carry out a polymerization reaction to obtain PS-SiO2-OH Janus nanoparticles; the emulsion system comprises water, an organic solvent, an emulsifier, a silica precursor and a mercaptosilane coupling agent; wherein the silica precursor is pre-dissolved in the water phase, and the silane coupling agent is pre-dissolved in the oil phase; during the emulsion formation process, the silane coupling agent in the oil phase is hydrolyzed and migrates to the oil-water interface, captures SiO2 generated in the water phase and reacts with it, and finally forms SiO2 with Janus characteristics, i.e., PS-SiO2-OH Janus nanoparticles; styrene molecules are dissolved in the oil phase of the emulsion, and under the action of the initiator, the polymerization reaction is initiated by heating; (2) The PS-SiO2-OH Janus nanoparticles are modified by a silane coupling agent containing an epoxy functional group to obtain PS-SiO2-Epoxy Janus nanoparticles, which are Janus nanoparticle compatibilizers.
[0012] The Janus nanoparticles prepared by the emulsion reaction of the present application have strong controllability and can be prepared in large quantities. The present invention prepares SiO2 nanoparticles grafted with polystyrene at one end and epoxy groups at the other end, and can anchor the Janus nanoparticles at the interface of the polymer phases by melt blending, effectively improving the compatibility of the composite material, thereby achieving a good volume expansion effect. During the melt blending process, the nanoparticles form a three-dimensional network structure as the polymer co-continuous structure is generated, which acts as a barrier to prevent the movement of the polymer at high temperature, and can effectively inhibit phase coarsening and phase separation.
[0013] Preferably, in step (1), the emulsion system is constructed by: dissolving an emulsifier and a silica precursor in water to form an aqueous phase, mixing a mercaptosilane coupling agent with an organic solvent to form an oil phase, and adding the oil phase dropwise into the aqueous phase for emulsification reaction to obtain an emulsion system.
[0014] Preferably, the concentration of the silica precursor in the aqueous phase is 0.01-0.1 g / L, more preferably 0.05 g / L.
[0015] Preferably, the concentration of the emulsifier in the aqueous phase is 0.1-0.5 g / L, more preferably 0.3 g / L.
[0016] Preferably, in step (1): the silicon dioxide precursor is selected from one or more of tetramethyl silicate, tetraethyl silicate and isopropyl orthosilicate.
[0017] Preferably, in step (1): the mercaptosilane coupling agent is γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane.
[0018] Preferably, in step (1): the emulsifier is selected from one or more of sodium dodecyl sulfate, sodium hexadecyl sulfate, hexadecyltrimethylammonium bromide, sodium stearate, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride.
[0019] Preferably, in step (1), the organic solvent is selected from one or more of cyclohexane, n-hexadecane, petroleum ether, n-heptane and n-decane.
[0020] Preferably, in step (1), the initiator is diisobutyl azo.
[0021] Preferably, in step (1): the epoxy functional group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0022] Preferably, the molar ratio of the silica precursor to the mercaptosilane coupling agent is (2-10):1.
[0023] Preferably, the mass ratio of styrene to silica precursor is (1-5):1, more preferably 2:1.
[0024] Preferably, the mass ratio of styrene to azobisisobutyl is 100:(0.5-2), more preferably 100:0.5.
[0025] Preferably, in step (1), the polymerization reaction temperature is 25-80°C.
[0026] Preferably, a post-treatment process is further included after the polymerization reaction, and the treatment process includes demulsification, centrifugation, washing and drying.
[0027] More preferably, sodium chloride is used for demulsification and ethanol is used for washing.
[0028] Preferably, in step (2), when the PS-SiO2-OH Janus nanoparticles are modified by a silane coupling agent containing an epoxy functional group, the PS-SiO2-OH Janus nanoparticles are first dispersed in ethanol, and the concentration of the PS-SiO2-OH Janus nanoparticles in ethanol is 10-50 g / L, more preferably 25 g / L.
[0029] The invention also provides a Janus nanoparticle compatibilizer prepared by the preparation method.
[0030] Preferably, the Janus nanoparticle compatibilizer comprises SiO2 particles, one end of the SiO2 particles is grafted with polystyrene (PS), and the other end of the SiO2 particles is grafted with epoxy groups.
[0031] More preferably, the particle size of the SiO2 particles is 20-50 nm.
[0032] More preferably, the particle size of the polystyrene is 50-100 nm.
[0033] Preferably, the Janus nanoparticles are in the shape of a snowman, and are composed of polystyrene (PS) spheres with a particle size of 50-100 nm and SiO2 spheres with a particle size of 20-50 nm, wherein one end of the SiO2 sphere is grafted with polystyrene and the other end is grafted with an epoxy group.
[0034] The present invention also provides an application of the Janus nanoparticle compatibilizer in the compatibilization and foaming of styrene and its incompatible blends, wherein the incompatible blends include polylactic acid and polystyrene, and the Janus nanoparticle compatibilizer accounts for 0.01-2wt% of the total mass of the blend.
[0035] The Janus nanoparticle compatibilizer of the present invention is a SiO2 nanoparticle with polystyrene grafted on one end and epoxy group grafted on the other end. The Janus nanoparticle can be anchored at the interface between two phases of polymer by a melt blending method, thereby effectively improving the compatibility of the composite material, thereby achieving a good compatibilization effect. During the melt blending process, the nanoparticle forms a three-dimensional network structure as the polymer co-continuous structure is generated, and acts as a barrier to prevent the movement of the polymer at high temperature, thereby effectively inhibiting phase coarsening and phase separation.
[0036] Preferably, polylactic acid, polystyrene and the Janus nanoparticle compatibilizer are melt-blended, compression-molded and autoclave-foamed to obtain a blend foam; the mass ratio of the polylactic acid to the polystyrene is 1:1.
[0037] Preferably, the melt blending equipment is a Haake torque rheometer, the blending temperature is 180-200°C, the rotation speed is 20-60 rpm, polylactic acid is first added and reactively blended with the Janus nanoparticles for 2-10 min, and then polystyrene is added and blended for 5-10 min. The purpose of adding polylactic acid first is to allow the epoxy group to fully react with the polylactic acid.
[0038] Preferably, the compression molding temperature is 180-200° C., the pre-compression pressure is 2-5 MPa, the pre-compression time is 2-5 min, the holding pressure is 10-15 MPa, and the holding time is 2-5 min.
[0039] Preferably, the autoclave pressure foaming method adopts a supercritical carbon dioxide foaming method.
[0040] More preferably, the supercritical carbon dioxide immersion temperature is 140-160°C, the supercritical carbon dioxide saturation time is 1-2 h, the saturation pressure is 5 MPa-14 MPa, and the foaming temperature is 80-120°C.
[0041] As described above, the present invention has the following beneficial effects: (1) The Janus nanoparticle extender prepared by emulsion reaction has strong controllability and can be prepared in large quantities; (2) The organic-inorganic hybrid Janus nanoparticle compatibilizer prepared by the process of the present invention can be used for the compatibilization and foaming of styrene and its incompatible blends. For example, when used for compatibilization of polylactic acid / polystyrene materials, the nanoparticles can be anchored at the interface of the two phases to form a barrier connecting the two phases. In the supercritical carbon dioxide foaming process, it can not only inhibit the coarsening process of the two phases at high temperature, but also play a role in heterogeneous nucleation in the pore formation stage; (3) The present invention also studies the effect of Janus nanoparticle compatibilizer on the foaming process and pore structure of the blend, providing a theoretical basis and practical guidance for the development of high-performance blended foaming materials, which has important application prospects and scientific significance in the fields of environmentally friendly materials, high-performance polymer materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Shown are the TEM (left) and EDS images (middle and right) of PS-SiO2-OH Janus nanoparticles in Example 3.
[0043] Figure 2 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Application Example 1.
[0044] Figure 3 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Application Example 2.
[0045] Figure 4 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Application Example 3.
[0046] Figure 5 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Comparative Example 1.
[0047] Figure 6 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Comparative Example 2.
[0048] Figure 7 Shown is the SEM image of the PLA / PS / Janus nanoparticle foamed material in Comparative Example 3. DETAILED DESCRIPTION
[0049] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0050] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0051] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0052] Example 1 The present application embodiment provides a method for preparing a Janus nanoparticle compatibilizer, comprising the following steps: (1) Dissolve 2 g of tetraethyl silicate and 0.08 g of sodium dodecyl sulfate in 40 ml of deionized water as the aqueous phase of the emulsion reaction, add 0.25 g of 3-mercaptopropyltrimethoxysilane to 0.4 g of n-hexadecane (HD) as the oil phase of the emulsion reaction, add the oil phase dropwise to the aqueous phase, stir for 15 min, and emulsify in a cell crusher at 500 W for 10 min to obtain a mixed emulsion. Transfer to a 60°C water bath, stir magnetically at 400 rpm, and add ammonia water to adjust the solution pH to 9. After nitrogen is introduced for 2 h, ice is added for cooling, 4 g of styrene and 0.08 g of azobisisobutyl are slowly added, stirred in a 25°C water bath for 2 h, heated to 60°C, introduced for 8 h, and the product is demulsified, centrifuged, washed, and dried to obtain PS-SiO2-OH Janus nanoparticles; (2) Disperse 2 g of PS-SiO2-OH Janus nanoparticles in 200 ml of ethanol, add 20 ml of γ-glycidyloxypropyltrimethoxysilane, and stir magnetically for 18 h in a 70 °C oil bath. Filter, wash, and dry the product to obtain PS-SiO2-Epoxy Janus nanoparticles, which are Janus nanoparticle extenders.
[0053] Example 2 The difference between Example 2 and Example 1 is that the amount of 3-mercaptopropyltrimethoxysilane added is different, specifically 0.5 g, and the rest of the processes are exactly the same.
[0054] Example 3 The difference between Example 3 and Example 1 is that the amount of 3-mercaptopropyltrimethoxysilane added is different, specifically 0.75 g, and the rest of the processes are exactly the same.
[0055] The TEM and EDS images of the PS-SiO2-OH Janus nanoparticles prepared in this example are as follows: Figure 1 As shown by Figure 1 It can be seen that the prepared PS-SiO2-OH nanoparticles have a Janus structure. The nanoparticles are in the shape of a snowman, and one end is mainly composed of carbon elements. From the reaction principle, it can be known that it is polystyrene (PS), and the other end is mainly composed of silicon elements. From the reaction principle, it can be known that it is silicon dioxide (SiO2).
[0056] Example 4 The difference between Example 4 and Example 1 is that the types of components of the emulsion system are different, specifically: the silica precursor is isopropyl orthosilicate, the emulsifier is octadecyltrimethylammonium chloride, the organic solvent is petroleum ether, and the mercaptosilane coupling agent is γ-mercaptopropyltriethoxysilane, and the rest of the processes are exactly the same.
[0057] Example 5 The difference between Example 5 and Example 1 is that in step (2), the concentration of the PS-SiO2-OH Janus nanoparticles in ethanol is different, specifically 25 g / L, and the rest of the process is exactly the same.
[0058] Example 6 The difference between Example 6 and Example 1 is that in step (1), the mass ratio of styrene to azobisisobutylene is different, specifically 100:0.5, and the rest of the processes are exactly the same.
[0059] Application Example 1 The application example of the present application also provides an application of a Janus nanoparticle compatibilizer in preparing a foaming material, including: S1: 0.5 g of the Janus nanoparticle compatibilizer prepared in Example 2 and 25 g of polylactic acid were added to a Haake torque rheometer for blending at a blending temperature of 190°C and a rotation speed of 60 rpm. After 4 minutes, 25 g of polystyrene was added and melt blended for 4 minutes. The sample was then molded at 180°C using a tablet press to obtain a plate sample.
[0060] S2: The plate sample was placed in a supercritical gas foaming reactor and maintained at 150°C and 10 MPa for 1 h, then rapidly cooled to 80°C, stabilized for 10 min, and then rapidly released the pressure to obtain a PLA / PS / Janus nanoparticle foaming material. Its SEM image is shown in Figure 2 shown.
[0061] Application Example 2 The difference between Application Example 2 and Application Example 1 is that in S2, the foaming temperature is different, specifically 100°C, and the rest of the processes are exactly the same. The SEM image of the obtained PLA / PS / Janus nanoparticle foamed material is as follows: Figure 3 shown.
[0062] Application Example 3 The difference between Application Example 3 and Application Example 1 is that in S2, the foaming temperature is different, specifically 120°C, and the other processes are exactly the same. The SEM image of the obtained PLA / PS / Janus nanoparticle foamed material is as follows: Figure 4 shown.
[0063] Application Comparative Example 1 The difference between the comparative example 1 and the example 1 is that the Janus nanoparticle compatibilizer prepared in example 2 is not added to S1, and the other processes are exactly the same. The SEM image of the obtained PLA / PS foaming material is as follows: Figure 5 shown.
[0064] Application Comparative Example 2 The difference between Application Comparative Example 2 and Application Example 2 is that the Janus nanoparticle compatibilizer prepared in Example 2 is not added to S1, and the rest of the processes are exactly the same. The SEM image of the obtained PLA / PS foamed material is as follows: Figure 6 shown.
[0065] Application Comparative Example 3 The difference between Application Comparative Example 3 and Application Example 3 is that the Janus nanoparticle compatibilizer prepared in Example 2 is not added to S1, and the other processes are exactly the same. The SEM image of the obtained PLA / PS foamed material is as follows: Figure 7 shown.
[0066] contrast Figure 2 and Figure 5It can be seen that the pores in the sample are polylactic acid (PLA) phase, and the unfoamed phase is polystyrene (PS) phase. It can be observed that the added Janus nanoparticle compatibilizer can effectively inhibit phase aggregation, and the unfoamed polystyrene is evenly distributed and easier to disperse stress.
[0067] Combination Figure 3 , Figure 4 , Figure 6 and 7 It can be seen that in the PLA / PS system with 1 Phr Janus nanoparticle compatibilizer added, the large and small bubbles can be evenly distributed in the foamed sample; in the PLA / PS system without the Janus nanoparticle compatibilizer added, serious phase aggregation occurs in the foamed sample, and the small bubbles obtained by polystyrene (PS) foaming cannot be evenly distributed.
[0068] The PLA / PS / Janus nanoparticle foaming materials prepared by using Examples 1 to 3 and the PLA / PS foaming materials prepared by using Comparative Examples 1 to 3 were characterized, and the results are shown in Table 1: Table 1. Test results of foam materials obtained by using Examples 1 to 3 and Comparative Examples 1 to 3 The above examples are for the purpose of illustrating the embodiments disclosed by the present invention and are not to be construed as limitations of the present invention. In addition, the various modifications listed herein and the variations of methods and compositions in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been specifically described in conjunction with various specific preferred embodiments of the present invention, it should be understood that the present invention should not be limited to these specific embodiments. In fact, various modifications obvious to those skilled in the art as described above to obtain the invention should be included within the scope of the present invention.
Claims
1. A method for preparing a Janus nanoparticle compatibilizer, characterized in that: The following steps are involved: (1) adding styrene and an initiator to an emulsion system to carry out a polymerization reaction to obtain PS-SiO2-OH Janus nanoparticles; the emulsion system comprises water, an organic solvent, an emulsifier, a silica precursor and a mercaptosilane coupling agent; (2) The PS-SiO2-OH Janus nanoparticles are modified by a silane coupling agent containing an epoxy functional group to obtain PS-SiO2-Epoxy Janus nanoparticles, which are Janus nanoparticle compatibilizers.
2. The preparation method according to claim 1, characterized in that: In step (1), the emulsion system is constructed by: dissolving an emulsifier and a silica precursor in water to form an aqueous phase, mixing a mercaptosilane coupling agent with an organic solvent to form an oil phase, and adding the oil phase dropwise into the aqueous phase for emulsification reaction to obtain an emulsion system; the concentration of the silica precursor in the aqueous phase is 0.01-0.1 g / L, and the concentration of the emulsifier in the aqueous phase is 0.1-0.5 g / L.
3. The preparation method according to claim 1, characterized in that: In step (1): The silicon dioxide precursor is selected from one or more of tetramethyl silicate, tetraethyl silicate and isopropyl orthosilicate; The mercaptosilane coupling agent is γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane; The emulsifier is selected from one or more of sodium lauryl sulfate, sodium cetyl sulfate, cetyltrimethylammonium bromide, sodium stearate, cetyltrimethylammonium chloride and octadecyltrimethylammonium chloride; The organic solvent is selected from one or more of cyclohexane, n-hexadecane, petroleum ether, n-heptane and n-decane; The initiator is diisobutyl azo; The epoxy functional group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the silica precursor to the mercaptosilane coupling agent is (2-10):1; the mass ratio of styrene to the silica precursor is (1-5):1; and the mass ratio of styrene to azobisisobutyl is 100:(0.5-2).
5. The preparation method according to claim 1, characterized in that: In step (1), the polymerization reaction temperature is 25-80° C.; and after the polymerization reaction, a post-treatment process is also included, and the treatment process includes demulsification, centrifugation, washing, and drying.
6. The preparation method according to claim 4, characterized in that: In step (2), when the PS-SiO2-OH Janus nanoparticles are modified by a silane coupling agent containing an epoxy functional group, the PS-SiO2-OH Janus nanoparticles are first dispersed in ethanol, and the concentration of the PS-SiO2-OH Janus nanoparticles in ethanol is 10-50 g / L.
7. A Janus nanoparticle compatibilizer prepared by the preparation method according to any one of claims 1 to 6.
8. A use of the Janus nanoparticle compatibilizer as claimed in claim 7 in the compatibilization and foaming of styrene and its incompatible blends, characterized in that: The Janus nanoparticle compatibilizer accounts for 0.01-2 wt % of the total mass of the blend.
9. The use according to claim 8, characterized in that: Polylactic acid, polystyrene and the Janus nanoparticle compatibilizer are melt-blended, compression-molded and autoclave-pressed to obtain a blend foam; the mass ratio of the polylactic acid to the polystyrene is 1:
1.
10. The use according to claim 9, characterized in that: The melt blending equipment is a Haake torque rheometer, the blending temperature is 180-200° C., the rotation speed is 20-60 rpm, polylactic acid is first added and reactively blended with the Janus nanoparticles for 2-10 min, and then polystyrene is added and blended for 5-10 min; The compression molding temperature is 180-200°C, the pre-compression pressure is 2-5 MPa, the pre-compression time is 2-5 min, the holding pressure is 10-15 MPa, and the holding time is 2-5 min; The autoclave pressure foaming method adopts the supercritical carbon dioxide foaming method, the supercritical carbon dioxide immersion temperature is 140~160℃, the supercritical carbon dioxide saturation time is 1~2h, the saturation pressure is 5MPa~14MPa, and the foaming temperature is 80~120℃.
Citation Information
Patent Citations
Janus nano material with double properties and preparation method of Janus nano material
CN103204508A